Lanthanide Complexation of 2, 6‐Bis(5, 6‐dipyridyl‐1, 2, 4‐triazinyl)pyridine – Solvent‐ and Lanthanide‐Ion‐Controlled Ligand Coordination Mode and Denticity. Issue 6 (25th January 2016) - Bhattacharyya, Arunasis; Forster, Paul M.; Rego, Daniel B.; Czerwinski, Kenneth R.
Abstract: 2, 6‐Bis(5, 6‐dipyridyl‐1, 2, 4‐triazinyl)pyridine (PyBTP) is an interesting ligand owing to the possible variation of its coordination sites and denticity in complexation. Therefore, solution and solid‐phase lanthanide complexations were studied with PyBTP in two solvents, viz., acetonitrile and methanol, through various spectroscopic and single‐crystal X‐ray diffraction techniques. The results from all of these studies consistently showed the interesting observation of solvent‐dependent changes to the ligand coordination mode and denticity, which are reported for the first time for trivalent lanthanide (Ln 3+ ) complexes. The ligand coordination is affected by the size of the lanthanide ion. This observation can provide clues for the development of intra‐lanthanide and lanthanide–actinide separation methods through the exploitation of the variable complexing behaviour of a particular ligand. Abstract : Solvent‐ and metal‐ion‐dependent changes in the ligand coordination mode and denticity in the lanthanide complexes of 2, 6‐bis(5, 6‐dipyridyl‐1, 2, 4‐triazinyl)pyridine (PyBTP) are investigated through fluorescence spectroscopy, 1 H NMR spectroscopy, UV/Vis spectrophotometry, attenuated total reflectance (ATR) FTIR spectroscopy, and single‐crystal XRD.